(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The advantage of the production process of the production of liquid wall paper and the cellulose obtained from the fibrous waste included in it and the reagents synthesized on its basis is superior to the existing technologies, in the fact that it has high quality indicators due to the reduction of several processes during its synthesis, as well as the physico-chemical and mechanical properties of the product obtained by the existing technology. it is distinguished by its absence.